fPCM Selection for Latent Heat Storage by MCDM - Martìnez-Gomez, Javier (2020)
A common complication in industry is the difference between available thermal energy and its application period. Using thermal energy storage with phase change materials (PCMs) will increase considerably the energy efficiency in industry and will solve the gap between energy supply and consumption. This research aims to select a PCM which better accomplish the solution of the TES between 200–400 °C and reduce the cost of production. MCDM have been developed to resolve the problem. The MCMD methods were complex proportional assessment of alternatives such as COPRAS-G, TOPSIS and VIKOR methods. The criteria weighting was performed by AHP and Entropy method. The correlation of the results between three ranking methods has been developed by the Spearman’s correlation coefficient. The results illustrated the best choices of the three MCDM were NaOH and KNO3, due to the highest values of the most important criteria. Furthermore, Spearman’s correlation between both methods exceeds 0,714.